Does congruence between incentive system and locus of control affect team performance? - Mutmainah, Siti; Sugiri, Slamet (2017)
Teamwork is an essential element in most organizations; however, little is known about the best fit among incentive system, team composition, and team performance.This study examines whether the congruence between incentive system and locus of control (LoC) affects team performance.To reconcile opposite lines of arguments regarding the best incentive system for a team, this paper uses the social identity perspective and person-environment fit theory to understand behavior in a group process. One hundred and five postgraduate students were assigned to three-person work groups, where they completed an independent task under one of two types of incentive—individual and group incentive— after their LoC was measured.Results suggest that group incentive results in an enhanced team performance and team performance is better when there is congruence between incentive system and LoC.Group incentive system combined with external LoC results in the best performance, while individual incentive results in a better team performance when combined with internal LoC.